Trichoderma in the promotion of growth and nutrition of dwarf cashew rootstock - Marcos Rodrigues dos Santos, João (Revista Ciência Agronômica, 2021)
Inoculation of microorganisms in plants performs important functions related to plant growth and nutrition.The responses are based on hormonal stimulation and improved absorption and effi ciency in the use of nutrients. Thus, theobjective of this study was to evaluate the ability of Trichoderma strains (T. longibrachiatum and T. asperellum) to promotegrowth and improve the nutrition in dwarf cashew rootstock. The experiment was conducted in a shade net house with 50%of shading located in the Experimental Field of Pacajus, belonging to Embrapa Agroindústria Tropical, in Pacajus/CE, Brazil.The experimental design used was completely randomized, with three treatments and ten replicates. Each experimental unitconsisted of a tube with a 288 cm3capacity containing one seedling of dwarf cashew. At sixty days (60) after germination,the plants were evaluated for biometric parameters, Dickson’s quality index, and nutritional diagnosis of leaves. To verify thegrowth-promoting mechanisms, the strains were reisolated by indirect plating of roots. Nutrient accumulation in the leaveswas not infl uenced by the application of the isolates; however, the seedlings were adequately supplied. The strains showedsimilarities in relation to growth-promotion mechanisms. The Trichoderma longibrachiatum strain promoted an increase in thegrowth, so its use as a supplement for the planting substrate is recommended.